Business Model Financial Technology Design by using Business Model Canvas based on Consumption Values Model (Case Study OVO user in Surabaya City) - Novianti, Fenty Dwi; Wulandari, Sri Hariani Eko; Wardhanie, Ayouvi Poerna (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2021)
The development of e-business has led to the emergence of a new business model, namely Financial Technology, which helps the public to be able to obtain financial transaction services quickly and easily. However, not many companies know how to design the right business model, especially fintech. Therefore, this research was conducted to design a financial technology business model using a business model canvas based on the consumption values of a case study of OVO application users in the city of Surabaya. The Business Model Canvas has 9 elements to be used, namely Customer Segments, Value Propositions, Channels, Customer Relationships, Revenue Streams, Key Resources, Key Activities, Key Partnerships and Cost Structure, while the Consumption Value has 5 elements to be used, namely Functional Value, Social Values, Emotional Values, Epistemic Values, and Conditional Values. In this study, OVO is used as an object of research because it is one of the most successful fintechs in Indonesia. The sample in this study used Simple Random Sampling with a sample size of 100 respondents and the technique for analysing the data used SEM (Structural Equation Modelling). The results showed that Functional Value significant all nine elements in BMC, while Social Value significant Channels, Emotional Value significant Key Resources and Key Activities, Epistemic Value significant Channels and Customer Relationships, Conditional Value significant Customer Segments, Value Propositions, Key Resources and Key Partnerships.